The influence of social policies on attitudes and behavior in times of rising inequalities and climate change - Parth, Anne-Marie (2023)
This cumulative dissertation engages in the cross-country effect of social policies on environmental and political attitudes and behaviour. While the first two papers deal with the welfare-environment nexus, by asking how economically deprived groups can be motivated for climate action through generous social policies (see chapter 3 and 4), the last two papers deal with backlashing and with the unexpected consequences reducing inequalities and testing new social security systems can have (see chapter 5 and 6). Chapter 5 asks how reducing gender inequalities affects political orientation, while chapter 6 – assuming that rising social inequalities require thinking of new social solutions – tests whether welfare experiments provide a suitable policy instrument for evidence-based policy making in times of rising inequalities.